DESAIN SISTEM REMINDER UNTUK PASIEN PROGRAM PENGELOLAAN PENYAKIT KRONIS (PROLANIS): Indonesia - Subayu, Abdi; Kusumadewi, Sri; Kurniawan, Rahadian (UII, 2025)
This study aims to develop a reminder application system for patients with hypertension and diabetes mellitus (DM) to improve medication adherence and health monitoring. Hypertension and diabetes are non-communicable diseases whose prevalence continues to rise in Indonesia, with Puskesmas Ngaglik 1 as the study location showing low patient compliance with the chronic disease management program (Prolanis). Using the User Centered Design (UCD) method, this research involves users at every stage of system development, from problem identification, literature review, to prototype creation. The results indicate that the developed application can assist patients in remembering their medication schedules, routine check-ups, and exercise, as well as providing emergency features to enhance interaction between patients and Prolanis staff. Prototype evaluation was conducted through two iterations, demonstrating that the resulting system meets user needs. Users say that the system built can help in the Prolanis program and improve discipline in patients.